2015
DOI: 10.1017/s2040174415007965
|View full text |Cite
|
Sign up to set email alerts
|

The effect of maternal and post-weaning low and high glycaemic index diets on glucose tolerance, fat deposition and hepatic function in rat offspring

Abstract: 24Clinical studies have reported beneficial effects of a maternal low glycaemic index (GI) diet 25 on pregnancy and neonatal outcomes, but the impact of the diet on the offspring in later life, 26 and the mechanisms underlying these effects, remain unclear. In this study, Albino Wistar rats 27 were fed either a low GI (n=14) or high GI (n=14) diet during pregnancy and lactation and their 28 offspring weaned onto either the low or high GI diet. Low GI dams had better glucose tolerance offspring, but the male lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 34 publications
2
17
1
Order By: Relevance
“…The systematic search procedure with the number of articles included and excluded at each point is depicted in Figure 1 . The end result was 30 articles, with 15 [ 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 ] involving mice, 13 [ 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 ] involving rats and two [ 56 , 57 ] with experiments performed on both species. Of the articles that contained pertinent results, all contained information regarding the change or comparison of body weight or fat, and most examined some measure of glucose homeostasis.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The systematic search procedure with the number of articles included and excluded at each point is depicted in Figure 1 . The end result was 30 articles, with 15 [ 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 ] involving mice, 13 [ 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 ] involving rats and two [ 56 , 57 ] with experiments performed on both species. Of the articles that contained pertinent results, all contained information regarding the change or comparison of body weight or fat, and most examined some measure of glucose homeostasis.…”
Section: Resultsmentioning
confidence: 99%
“…The average score, out of 22, for each species was 13.3 and 12.2, respectively, to one decimal place. There was a small amount of variation in the quality of the articles, with the vast majority having a score between 11 and 16, inclusive [ 28 , 29 , 30 , 32 , 34 , 35 , 36 , 37 , 41 , 42 , 43 , 44 , 45 , 47 , 49 , 50 , 51 , 52 , 54 , 55 , 56 , 57 ], and a lowest score of 8 [ 38 ] and highest of 18 [ 31 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…12 We have also previously reported that PC:EtOH causes fetal growth restriction 25 and postnatal catch up growth 12 both of which have been associated with increased fat deposition and risk of obesity in many previous studies. [26][27][28] However, a gold standard measurement such as dual-energy X-ray absorptiometry would be needed to confirm these findings. As our rats were studied at quite an advanced age it is important to note that differential fat deposition could have occurred during other periods of development and adulthood that we did not investigate.…”
Section: Discussionmentioning
confidence: 99%
“…This was unexpected in light of our previous finding that periconceptional alcohol exposure is associated with elevated fasted plasma glucose, impaired glucose tolerance and decreased insulin sensitivity at 6 months of age (Gardebjer et al, 2015). We have also previously reported that PC:EtOH causes fetal growth restriction (Gardebjer et al, 2014) and postnatal catch up growth (Gardebjer et al, 2015) both of which have been associated with increased fat deposition and risk of obesity in many previous studies (Bellinger et al, 2006;Joss-Moore et al, 2010;Gugusheff et al, 2016a). However, a gold standard measurement such as dual-energy X-ray absorptiometry (DXA) would be needed to confirm these findings.…”
Section: Discussionmentioning
confidence: 78%